DTI-ALPS: An MR biomarker for motor dysfunction in patients with subacute ischemic stroke - Qin, Yue; Li, Xin; Qiao, Yanqiang; Zou, Huili; Qian, Yifan; Li, Xiaoshi; Zhu, Yinhu; Huo, Wenli; Wang, Lei; Zhang, Ming (Frontiers in Neuroscience, 2023)
Purpose The impaired brain glymphatic function is involved in the pathologic process of acute ischaemic stroke (IS). The relationship between brain glymphatic activity and function disruption in subacute IS is not completely understood. This study used diffusion tensor image analysis along the perivascular space (DTI-ALPS) index to explore whether human glymphatic activity was related to motor dysfunction in subacute IS patients. Methods This study recruited 26 subacute IS patients with a single lesion in the left subcortical regions and 32 healthy controls (HC). The intra-group and inter-group DTI-ALPS index and DTI metrics (fractional anisotropy, FA; mean diffusivity, MD) were compared. In the IS group, the relationships of the DTI-ALPS index with Fugl-Meyer assessment scores and corticospinal tract (CST) integrity were explored using Spearman and Pearson partial correlation analysis. Results Six IS patients and two HC were excluded. The left DTI-ALPS index of IS group was significantly lower than that of the HC group (t=-3.02, p=0.004). In the IS group, a positive correlation was found between the left DTI-ALPS index and the simple Fugl-Meyer motor function score (ρ=0.52, p=0.019), and the significant negative correlations between the left DTI-ALPS index and the FA (R=-0.55, p=0.023) and MD (R=-0.48, p=0.032) value of the right CST were also found. Conclusions The impaired glymphatic function is involved in the subacute IS. DTI-ALPS could be a potential MR biomarker of motor dysfunction for subacute IS patients. These findings contribute to further understanding the pathophysiological mechanism of IS and provide a new target for alternative treatment of IS.